Enhancing Legal Awareness in Women Inmates for Effective Resocialization - Fitri Wahyuni; Siti Rahmah; Syarifuddin Syarifuddin (Indonesian Journal of Cultural and Community Development, 2024)
This meeting focuses on the development of legal awareness in women inmates at the Class II A Tembilahan Correctional Institution, Indonesia. Emphasizing the importance of legal education in the resocialization process, it adopts a methodical approach involving educational sessions, seminars, and counseling, tailored to the specific needs and backgrounds of the inmates. The primary goal is to deepen understanding and foster compliance with legal norms, aiding their integration back into society. The findings reveal significant improvements in legal awareness among the inmates, leading to better social behavior and reduced recidivism rates. This approach suggests a positive correlation between targeted legal education and successful resocialization, highlighting its potential as a standard practice in correctional systems. The implications are far-reaching, suggesting a need for wider implementation and further research into its long-term effects on reducing crime rates and enhancing societal harmony.Highlights: The meetings underscores the crucial role of legal education in the rehabilitation and resocialization of women inmates. It demonstrates a positive impact of structured educational programs on improving legal awareness and social behavior among inmates. The research suggests the potential for expanding such educational initiatives to other correctional facilities for broader societal benefits. Keywords: Legal Awareness, Women Inmates, Resocialization, Correctional Education, Rehabilitation